2018
DOI: 10.3390/rel9080243
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Victimisation among Muslim Adolescents in the UK: The Effect of Psychological and Religious Factors

Abstract: This study set out to explore the levels of victimisation experienced by Muslim adolescents in the UK, the extent to which victimisation is conceptualised in religious terms, and the extent to which individual differences in the experience of victimisation is related to personal factors, psychological factors and religious factors. Data provided by 335 13- to 15-year-old Muslim students from England, Northern Ireland, Scotland and Wales demonstrated that one in four Muslim students (25%) reported being bullied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…With regard to this educational problem, Pottie et al (2015) found that the consequences of discrimination are more negative for members of disadvantaged groups. Additionally, the majority of harassment experiences are inflicted on ethnic minorities (Rhee et al 2017) or those people with a different religion to the majority (Francis and McKenna 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this educational problem, Pottie et al (2015) found that the consequences of discrimination are more negative for members of disadvantaged groups. Additionally, the majority of harassment experiences are inflicted on ethnic minorities (Rhee et al 2017) or those people with a different religion to the majority (Francis and McKenna 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The item endorsements indicated overall a high level of personal happiness among the young churchgoers with at least four out of every five participants expressing happiness with six of the ten domains itemised in the instrument: 88% were happy about how they were getting on with the people they know, and 83% were happy with their life as a whole. The fact that the proportion dropped to 77% who were happy with their school may indicate the potential tensions between faith and schooling (see Francis & McKenna, 2019). These data suggest that the new 10-item instrument introduced into the 2016 NCLS Children's Survey is an improvement over the 4-item measure employed in the 2011 NCLS Children's Survey (α = .62).…”
Section: Resultsmentioning
confidence: 92%
“…For example, Francis and Robbins (2005) demonstrated that students who self-identified as Christian recorded higher levels of anxiety about being bullied at school, compared with religiously unaffiliated students. In a more recent study Francis and McKenna (2019) focused specifically on the experience of victimisation among a sample of 3,105 13-to 15-year-old students who selfidentified as Christian and who attended worship services at least six times a year apart from special occasions (like weddings). These data demonstrated that 14% reported being bullied Pentecostal churches, and 316 other Protestant churches, with the remaining 66 attending unspecified congregations.…”
Section: Introductionmentioning
confidence: 99%
“…The application, through the videos, shows different cultural realities that students can observe from a critical perspective [123][124][125]. The reflection of intercultural content can lead to students modifying racial or ethnic prejudices and changing their vision towards certain classmates, avoiding, in the worst case, discriminatory attitudes towards minority students [126,127].…”
Section: Discussionmentioning
confidence: 99%